Rapid, scalable, and low-cost purification of recombinant adeno-associated virus produced by baculovirus expression vector system - Pierre-Olivier Buclez (Molecular Therapy: Methods & Clinical Development, 2016)
Recombinant adeno-associated viruses (rAAV) are largely used for gene transfer in research, preclinical developments, and clinical trials. Their broad in vivo biodistribution and long-term efficacy in postmitotic tissues make them good candidates for numerous gene transfer applications. Upstream processes able to produce large amounts of rAAV were developed, particularly those using baculovirus expression vector system. In parallel, downstream processes present a large panel of purification methods, often including multiple and time consuming steps. Here, we show that simple tangential flow filtration, coupled with an optimized iodixanol-based isopycnic density gradient, is sufficient to purify several liters of crude lysate produced by baculovirus expression vector system in only one working day, leading to high titers and good purity of rAAV products. Moreover, we show that the viral vectors retain their in vitro and in vivo functionalities. Our results demonstrate that simple, rapid, and relatively low-cost methods can easily be implemented for obtaining a high-quality grade of gene therapy products based on rAAV technology.